Peningkatan Keaktifan dan Hasil Belajar Materi Mengindentifikasi Bangun Ruang dengan Menggunakan Pendekatan Contextual Teaching and Learning (CTL) pada Mata Pelajaran Matematika - Yunianto, Yunianto (Universitas Muhammadiyah Magelang, 2021)
The purpose of this study is to increase activity and the results of math study in the student class VI, where students will be able to be more active in math study and will be able to improve student's learning through the acquisition of a math daily test in the material identifying space. The study employed class action research methods. The research model used is a cycle model developed by Kemmis and Taggart. The research is run at SDN Kedungsari 5, manageable year study 2020/2021. The study subject was VI class of 32 children, among whom there were 13 male and 19 female students. The method of collecting data used is by using triangulation of methods and source triangulation, both of which are analyzed according to the research obtained that is by two ways: (1) quantitative data is analyzed using comparative deductions; and (2) qualitative data are analyzed using qualitative descriptions. The research is done in two cycles. Cycle I with the CTL approach through the big group discussion and cycle II uses the CTL approach by the assignment method and small group discussion. This research shows the application of a CTL approach to student class VI SDN class 5 manageable class 2020/2021 lesson year exactly 2nd semester, can increase activation and student learning results. This can be shown from the initial conditions of obtaining an average score of 62.06. Then in the first cycle, it can increase to 69.52 which at end of the average result of the end of the cycle test is 81.47. That way, the ability of teacher management in learning the CTL approach in class VI SDN Kedungsari 5 Magelang City has met the indicators of success.